Research on the Stability of Shallow-Buried Large Cross-Section Tunnel by Construction Method Conversion - Zhang, Zhiyong; Zhao, Chenyang; Peng, Long; Zhang, Xiaohui; Lei, Mingfeng (Frontiers in Earth Science, 2022)
The blind and random use of the combined construction method may have a great impact on tunnel stability. To determine the influence of construction method conversion on tunnel deformation and the reasonable conversion condition, a numerical model is established to simulate the construction method transforms from central diaphragm method to the benching tunneling method based on Jiaoweiqin Tunnel. The conversion condition is determined based on the results of tunnel geological prediction and in-site monitoring, and the temporary two-bench tunneling method is adopted to ensure the success of construction method conversion. Besides, the parameter analysis is done to analyze the influence of mechanical properties of surrounding rock mass and bench length on tunnel stability. Research results indicate that the construction safety should be evaluated before construction method conversion is carried out by analyzing the design blueprint, tunnel geological prediction results, geological survey reports, rock mass conditions in front of tunnel face, in-site monitoring data, and numerical simulation results. Meanwhile, the construction method conversion can be carried out in the order of central diaphragm method, two-bench tunneling method, and bench tunneling method. Parameter analysis results reveal that the deformation of primary support decreases in a negative exponential form with the increase in elasticity modulus and increases approximately linearly with the increase in bench length. For shallow buried and large cross-section tunnels, the tunnel deformation is in a small state when the elastic modulus of rock mass reaches a certain value. The construction method conversion can be carried out when the rock mass has a certain stability, and the length of construction method conversion should be small to ensure construction safety.